Detection of horizontal root fracture using four different protocols of cone-beam computed tomography - Fernanda Cristina Sales SALINEIRO; Lucas Rodrigues PINHEIRO; Oséas dos SANTOS JÚNIOR; Marcelo Gusmão Paraiso CAVALCANTI (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The purpose of this study was to analyze four different cone-beam computed tomography (CBCT) protocols to identify horizontal root fractures (HRF) in endodontically treated teeth, with or without the presence of a metallic post. Thirty extracted single-rooted human premolars were treated endodontically. Afterwards, an observer induced a horizontal fracture in 15 teeth. Each tooth was inserted in an empty mandibular socket and submitted to a computed tomography scan taken with and without the metallic post. The acquisition followed four different protocols, with different fields of view (FOV) and voxel sizes, as follows: FOV 6X16 cm/0.2 mm voxel; FOV 6X16 cm/0.25 mm voxel; FOV 8X8 cm/0.2 mm voxel; FOV 8X8 cm/0.25 mm voxel. Two observers checked all the acquisitions within a two-week interval, and the values of sensitivity, specificity, accuracy and kappa were calculated. The sensitivity, specificity and accuracy values were better for the 8X8 cm/0.2 mm and 16X6 cm/0.25 mm protocols, ranging from 0.60 to 0.86 and 0.53 to 0.80, respectively. The intra- and interobserver concordance ranged from 0.65 to 0.72. The protocols where FOV and voxel were proportional showed better results. The 8x8 cm/0.2 mm protocol had the least interference from the metallic artifact. All four protocols showed a decline in values in the presence of the metallic artifact.